India Digital Ecosystem of Agriculture and Agristack: An Initial Assessment - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
Creation of an Agristack has now, for some time, been identified as a necessary step for the realisation of the potential offered by Digital technologies and ICTs in Indian Agriculture. In order to create Agristack, the Indian Agriculture Ministry is in the process of finalising the "India Digital Ecosystem of Agriculture (IDEA)" which lays down a framework for building Agristack. The IDEA Ecosystem shall help the Government in effective planning towards increasing the income of farmers in particular and improving the overall efficiency of the Agriculture sector. In the process towards building the Agristack, the Ministry is undertaking pilot projects in collaboration with leading technology companies and "Agtechs".We summarise both the IDEA initiative and the pilots in this paper. We find that the IDEA ecosystem and the pilot projects are welcome initiatives. However, owing to some concerns around data and individual privacy that have been raised as well as the efficacy of solutions and the significant involvement of the private sector, continued transparency in all matters would serve the best interest of all concerned. It is hoped that the government adopts a consultative process with all stakeholders to resolve the genuine concerns. It should also seek continuous feedback of these initiatives through third party evaluations and independent studies so that a robust digital ecosystem in Indian Agriculture can be established that benefits the Indian farmer.
Keywords: 330